C-Fos Expression after Stochastic Vestibular Stimulation and Levodopa in 6-OHDA Hemilesioned Rats. (1st January 2020) - Samoudi, Ghazaleh; Nilsson, Andrea; Carlsson, Thomas; Bergquist, Filip
Highlights: Stochastic vestibular stimulation and levodopa increase c-fos in overlapping rat brain areas. Stochastic vestibular stimulation evokes stronger c-Fos activation in the vestibular nuclei after 6OHDA-hemilesions. The lateral habenula is a potential connection point between the vestibular system and the basal ganglia. Abstract: Near threshold stochastic vestibular stimulation (SVS) enhances postural control and improves other symptoms in neurodegenerative disorders like Parkinson's disease (PD). Improvement of postural control can tentatively be explained by increased responsivity of the vestibular system, but the mechanism behind other effects of near threshold SVS, like improved motor symptoms and cognitive responsiveness in PD, are not known. To better understand the effect of vestibular stimulation on brain activity in PD, c-Fos expression was used as a marker of change in functional activity following SVS in 6-hydroxydopamine (6-OHDA) hemi-lesioned and in sham-lesioned rats. The results were compared with the effect of a single levodopa injection in 6-OHDA hemi-lesioned or saline in sham-lesioned rats. SVS was found to increase c-Fos expression more than levodopa as well as saline in the parvocellular medial vestibular nucleus (MVePC) and more in 6-OHDA hemi-lesioned than in sham-lesioned animals. Furthermore, c-Fos expression increased more in the habenula nucleus (LHb) after SVS than it did after levodopa in 6-OHDA hemilesioned animals and after saline in the sham-lesioned animals. SVS and levodopa induced similar c-Fos expression in several regions, e.g. the caudate putamen (CPu), where saline had no effect. In conclusion there was overlap between SVS-activated areas and levodopa-activated areas, but activation was more pronounced following SVS in the MVePC of 6-OHDA lesioned and in the LHb in both lesioned and sham-lesioned rats.